Wives' right to the government retirement benefit: is it Syariah compliant or subject to fara`id distribution? - Abdullah, Mohamad Asmadi (Serials Publications, 2012)
The government retirement scheme is provided primarily as a financial facility for the pensionable government officers and their dependants upon retirement. However, the question whether it is subject to the fara’i distribution after the Muslim pensioner’s death is debatable. The current position is rather confusing because of the differences of opinion among Muslim scholars regarding whether or not the scheme is heritable upon death. Some jurists are of the view that the Malaysian Government’s current implementation of this scheme by imposing strict rules regarding the entitlement of specific persons including the surviving wife to the benefits after the death of a pensionable officer does not meet the Syariah (This the Malay version of the word Shari‘ah) principles, whereas according to others it does. This research is an attempt to analyse the related issues of the scheme in order to answer the question regarding its heritability in the case of Malaysia. The difference of opinion of Muslim scholars on this issue is examined. It has been observed that, unfortunately, most of these opinions are not based on convincing facts, and, furthermore, are not informative enough to provide Muslims an in- depth understanding of the verdicts.